Effect of the online module on leadership in knowledge acquisition among nursing students: A randomized controlled study protocol - Jucielly Ferreira da Fonseca; Silmara de Oliveira Silva; Louise Constância de Melo Alves Silva; Roberta Paolli de Paiva Oliveira Arruda Camara; Francisco de Cássio de Oliveira Mendes; Laura Lima Souza; Rodrigo Assis Neves Dantas; Daniele Vieira Dantas (PLoS ONE, 2025)
Leadership is an essential skill for success in nursing practice, influencing the nursing team’s organization, the quality of health services and decision-making in complex situations. The COVID-19 pandemic has further highlighted the need for leadership in nursing, with nurses playing a crucial role in addressing the crisis. However, there are challenges in leadership training, with conventional expository class methods often neglecting this skill. This study proposes to evaluate the impact of an online educational module focused on leadership for Nursing students, recognizing the importance of training future professionals from the beginning of their careers. To present a study protocol to evaluate the effect of an online educational module in comparison with a conventional expository class related to knowledge acquisition by Nursing students on the topic of Leadership. A Randomized Controlled Study, single-blind, two-arm will be conducted. Sixth semester students regularly enrolled in the nursing course will take part in the study. Participants will be randomly distributed into two groups, namely the Control Group, which will undergo a conventional class, and the Experimental Group, which will undergo an online educational module. Two important moments will be considered to evaluate the results of the intervention. A pesquisa, em fase de design, terá resultados, conclusões e análises definidos após a coleta de dados. The primary outcome is expected to demonstrate that the online module is equal to or superior to the conventional module in the acquisition of knowledge about leadership, addressing topics such as team involvement, organizational culture, conflict management and feedback. The secondary outcome will assess the acquisition of knowledge about leadership through an adaptation of the Nursing Student Self-Perception Questionnaire in the Exercise of Leadership.